Dichotomy in the Lithiation Pathway of Ellipsoidal and Platelet LiFePO4 Particles Revealed through Nanoscale Operando State‐of‐Charge Imaging. (12th May 2015) - Li, Yiyang; Weker, Johanna Nelson; Gent, William E.; Mueller, David N.; Lim, Jongwoo; Cogswell, Daniel A.; Tyliszczak, Tolek; Chueh, William C.
<x xml:space="preserve">Abstract</x> LiFePO4 is a promising phase‐separating battery electrode and a model system for studying lithiation. The role of particle synthesis and the corresponding particle morphology on the nanoscale insertion and migration of Li is not well understood, and elucidating the intercalation pathway is crucial toward improving battery performance. A synchrotron operando liquid X‐ray imaging platform is developed to track the migration of Li in LiFePO4 electrodes with single‐particle sensitivity. Lithiation is tracked in two particle types—ellipsoidal and platelet—while the particles cycle in an organic liquid electrolyte, and the results show a clear dichotomy in the intercalation pathway. The ellipsoidal particles intercalate sequentially, concentrating the current in a small number of actively intercalating particles. At the same cycling rate, platelet particles intercalate simultaneously, leading to a significantly more uniform current distribution. Assuming that the particles intercalate through a single‐phase pathway, it is proposed that the two particle types exhibit different surface properties, a result of different synthesis procedures, which affect the surface reactivity of LiFePO4. Alternatively, if the particles intercalate through nucleation and growth, the larger size of platelet particles may account for the dichotomy. Beyond providing particle engineering insights, the operando microscopy platform enables new opportunities for nanoscale chemical imaging of liquid‐based electrochemical systems.